Prospects and Problems of Tourism Industry in Sundarbans of Bangladesh - Rimon, Aftab Mahadi; Akhi, Nabila; Rina Aktar (Future Science, 2022)
Tourism is one of the ever-growing industries not only Bangladesh but also all around the world. Meanwhile, Sundarbans has considered as one of the best nature-based tourism sites in Bangladesh whilst few local peoples participate in this tourism sector. This study examines to analyze the present scenario of the tourism industry as well as identifying the different attractive tourist spots and its problems in the Sundarbans for analyzing the opportunities. Handling a self-administered interview schedule through convenience sampling, data were collected from 120 respondents who were obtained tourist spot in Sundarbans of Khulna Division. Findings showed that 88% tourist having knowledge about different tourist Spots of Sundarbans. The majority of the respondents (34%) visited to Koromjol and the other 29% in Herbaria, even 25% in Hiron Point. The different reasons of visiting a place, here, 46% tourist stayed this place along with 25% for place relaxation, even 17% for Study tour and 8% for research as well as 4% others purposes. The study clearly showed that satisfactory level of tourist of sundabans articulated by their ratings. 28% tourist are fully pleased, 35% tourist satisfactory level is good and 20% tourist are gratified. On the constant 13% tourist are dissatisfied and 4% tourist are very dissatisfied on the facilities on sundarbans. However, 33% tourist said developing infrastructure, 39% tourist ensuring tourist security, 17% tourist talking realistic policy as well as only 11% tourist suggested to other policy.